Voltaire on Shakespeare - Besterman, T (Voltaire Foundation, 2017)
Preface Introduction 1. from a letter to Thieriot (1726) 2. from the Lettres philosophiques (c.1729) 3. from the Discours sur la tragédie (1730) 4. from a letter to Cideville 5. from the Discours prononcé à l'Académie française (1746) 6. from the Dissertation sur la tragédie ancienne et moderne (1748) 7. from a letter by Patu to Garrick (1755) 8. from the Essai sur les mœurs (1756) 9. from a letter to Mme Du Deffand (1760) 10. from the Appel à toutes les nations de l'Europe (1761) 11. letter to [?] (1761) 12. from a letter to Keate (1762) 13. from a letter to Albergati Capacelli (1762) 14. from a letter to Saurin (1764) 15. review of lord Kames's Elements of criticism (1764) 16. from the commentary on Corneille's Médée (1764) 17. from the commentary on Corneille's Horaces (1764) 18. from the commentary on Corneille's Cinna (1764) 19. translation of Julius Caesar (1764) 20. from a letter to Saurin (1765) 21. from a letter to Horace Walpole (1768) 22. from 'Art dramatique' (1770) 23. from 'Goût' (1771) 24. conversation with Richard Neville (1772) 25. conversation with Martin Sherlock (1776) 26. from a letter to Argental (1776) 27. letter to Alembert (1776) 28. letter to Argental (1776) 29. letter to Alembert (1776) 30. letter to Alembert (1776) 31. letter to La Harpe (1776) 32. Lettre à l'Académie française (1776) 33. from a letter to Argental (1776) 34. letter to Alembert (1776) 35. from a letter to Condorcet (1776) 36. from a letter to Richelieu (1776) 37. from a letter to Necker (1776) 38. Lettre à l'Académie française (1777) Index of names